Synthesis of carbon nanoparticles/zinc oxide/zinc cobalt oxide composite and its electrochemical properties. Issue 11 (1st August 2020) - Shaikh, Hamid M.; Siva Kumar, Nadavala; Mahmood, Asif
Abstract: Carbon nanoparticles (CNP)/zinc oxide (ZnO)/zinc cobalt oxide (ZnCo2 O4 ) composite was synthesized using a hydrothermal method. Using XRD data, refinement was carried out by the Rietveld method to confirm the phase formations of ZnO and ZnCo2 O4 in the composite. The CNPs were identified using field emission scanning electron microscope images, which revealed their distribution on the ZnO/ZnCo2 O4 sheets, which was supported by TEM images. The surface state of the composite was identified to possess C, O, Co, and Zn elements, using X-ray photoelectron spectroscopy. Its surface area was measured to be 35.26 m 2 g -1 . To study the supercapacitor properties of the composite electrode, its electrochemical properties were measured, using cyclic voltammetry, galvanostatic charge–discharge curves, and electrochemical impedance spectroscopy. A specific capacitance of 593.6 F g −1 at 0.25 A g −1 was obtained for the composite electrode.